2013
DOI: 10.3386/w18833
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Means-tested Subsidies under Treatment Externalities with Application to Anti-Malarial Bednets

Abstract: Regular use of effective health-products such as insecticide-treated mosquito nets (ITN) by a household benefits its neighbors by (a) reducing chances of infection and (b) raising awareness about product-effectiveness, thereby increasing product-use. Due to their potential social benefits and high purchase price, causing free-riding and sub-optimal private procurement, such products may be subsidized in developing countries through means-testing. Owing to associated spillover effects, cost-benefit analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…One found evidence of negative spillovers, 46 eight found no evidence of spillovers 66–73 and eight found evidence of spillovers for some but not all outcomes or conditions reported. 21 , 37 , 38 , 50 , 74–77 These studies measured spillovers through four mechanisms among untreated individuals who were: (i) in areas where cash transfers were offered; (ii) in or near areas where subsidies or microloans were offered to promote certain health products or behaviours (e.g. subsidies for vaccines); (iii) socially connected to treated individuals; or (iv) in the same schools or areas as treated individuals, regardless of social links.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One found evidence of negative spillovers, 46 eight found no evidence of spillovers 66–73 and eight found evidence of spillovers for some but not all outcomes or conditions reported. 21 , 37 , 38 , 50 , 74–77 These studies measured spillovers through four mechanisms among untreated individuals who were: (i) in areas where cash transfers were offered; (ii) in or near areas where subsidies or microloans were offered to promote certain health products or behaviours (e.g. subsidies for vaccines); (iii) socially connected to treated individuals; or (iv) in the same schools or areas as treated individuals, regardless of social links.…”
Section: Resultsmentioning
confidence: 99%
“…Two of four studies evaluating spillovers of subsidies or microloans for health products found evidence of spillovers. 21 , 50 , 69 , 77 For example, in a study of incentives for immunization, Banerjee et al. estimated both total and spillover effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has made methodological progress in understanding how to most efficiently estimate externality effects, and how to address the possibility of nonlinearities in the relationship and complementarities with local treatment decisions. Bhattacharya et al (2013) exploit experimental variation combined with detailed geospatial information to estimate how the local subsidy rates faced by others affect insecticide-treated mosquito nets (ITN) use in Kenya, and show that there are important nonlinearities in the subsidy incidence. The issue of possible non-linearities in social effects are raised as a possibility in both and Kremer and Miguel (2007) but in neither study was there sufficient statistical power to reject linear specifications.…”
Section: Experimenting To Estimate Impacts Of Health Improvements: Bementioning
confidence: 99%
“…Kaier and Frank (2010) and Kaier (2012) ITNs and takes into account the benefits to non-users that live in the vicinity of users of ITNs (Cohen & Dupas, 2010). Bhattacharya, Dupas, and Kanaya (2013) found that when the indirect benefits of ITN subsidies to neighbors of users are ignored in cost-benefit analyses, ITN use is overestimated at lower and underestimated at higher subsidy rates. Cook et al (2009) show that if the optimal Pigouvian subsidy for Cholera vaccine is unknown, selling them at full marginal cost may, under some circumstances, be a preferable second-best option to providing them for free.…”
Section: How Big Are the Externalities?mentioning
confidence: 99%